Serum carbohydrate antigen 153 as a predictor of interstitial lung disease associated with rheumatoid arthritis is positively correlated with serum Krebs von den Lungen-6 - Jiaxi Guo; Heqing Huang; Shaowei Lin; Guangdong Wang; Fengbei Cen; Shenhui Huang; Dehao Liu; Yikai Lin; Xinhua Yu; Sien Shi; Aiping Ma (BMC Pulmonary Medicine)
Abstract Objective The objective of this study was to evaluate the clinical significance of carbohydrate antigen (CA) 153 and its correlation with Krebs von den Lungen-6 (KL-6) in the prediction and determination of the severity of interstitial lung disease (ILD) in rheumatoid arthritis (RA) patients. Methods Data was collected retrospectively on a cohort of 357 RA patients who were admitted to our hospital from January 2018 to December 2020. The classification of patients into subgroups was based on high-resolution computed tomography (HRCT) of the chest, resulting in 135 patients with RA but no ILD, 107 patients with RA and indeterminate ILD, 91 patients with RA and mild ILD, and 24 patients with RA and advanced ILD. The levels of CA153 and KL-6 were determined by chemiluminescence analysis. Results The serum levels of CA153 were found to be significantly higher in both the RA-mild ILD group and the RA-advanced ILD group compared to the RA-no ILD group (8.00 vs. 6.40, q = 0.039; 20.30 vs. 6.40, q < 0.001). Multivariate analysis demonstrated that CA153 was an independent risk factor for RA-ILD (RA-mild ILD + RA-advanced ILD) [odds ratio (OR) = 1.124, 95% confidence interval (CI) = (1.060–1.191), p < 0.001] and RA-advanced ILD (OR = 1.583, 95% CI = 1.247–2.010, p < 0.001). Furthermore, the receiver operating characteristic (ROC) analysis indicated that CA153 had diagnostic value for both RA-ILD (RA-mild ILD + RA-advanced ILD) and RA-advanced ILD. The best area under ROC curve (AUC) of CA153 for RA-ILD (RA-mild ILD + RA-advanced ILD) was 0.66 (p < 0.001; sensitivity = 57.27%; specificity = 72.03%). The AUC of CA153 for RA-advanced ILD was 0.95 (p < 0.001; sensitivity = 95.65%; specificity = 83.05%). Moreover, CA153 was negatively correlated with forced vital capacity percent predicted (FVC% pred) (r = -0.383, p = 0.037) but positively related to KL-6 (r = 0.762, p < 0.001). Conclusion It was concluded that CA153 was positively associated with KL-6 and might be a significant and clinical availably measurable serum marker to predict the diagnosis and severity of ILD in RA patients.